2021
DOI: 10.1007/s00259-021-05191-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between amyloid and tau levels and its impact on tau spreading

Abstract: Purpose Previous studies have shown that Aβ-amyloid (Aβ) likely promotes tau to spread beyond the medial temporal lobe. However, the Aβ levels necessary for tau to spread in the neocortex is still unclear. Methods Four hundred sixty-six participants underwent tau imaging with [18F]MK6420 and Aβ imaging with [18F]NAV4694. Aβ scans were quantified on the Centiloid (CL) scale with a cut-off of 25 CL for abnormal levels of Aβ (A+). Tau scans were quantified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
(23 reference statements)
6
39
0
Order By: Relevance
“…We found that a non-linear fit best explains the data, showing that a rise in detectable Aβ precedes a detectable increase in tau. We have previously shown that Aβ levels above ~50 CL are required to show significant cognitive and clinical change in cognitively normal older persons followed for 8 years (van der Kall, Truong et al 2020 point where a significant rise in the prevalence of T+ cases in CU as well as MCI and AD patients occurs (Dore, Krishnadas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We found that a non-linear fit best explains the data, showing that a rise in detectable Aβ precedes a detectable increase in tau. We have previously shown that Aβ levels above ~50 CL are required to show significant cognitive and clinical change in cognitively normal older persons followed for 8 years (van der Kall, Truong et al 2020 point where a significant rise in the prevalence of T+ cases in CU as well as MCI and AD patients occurs (Dore, Krishnadas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…All image processing was done locally. Images were realigned, averaged, resliced to 1.5mm 3 , and smoothed to a resolution of 8mm 3 FWHM. Each PET image was registered to the closest structural T1-weighted MRI image.…”
Section: Image Acquisition and Processing -Adnimentioning
confidence: 99%
“…Alzheimer’s disease (AD) is characterized by a cascade of molecular and neurodegenerative brain changes, in which Aβ plaques start to accumulate ∼20 years before symptom onset followed by the accumulation and spreading of neurofibrillary tau aggregates with ensuing neurodegeneration and AD dementia 1,2 . Multiple imaging studies of in vivo pathological processes with positron emission tomography (PET) in AD showed that cortical Aβ deposition precedes neocortical tau aggregation by several years 1,3 , and Aβ has been shown to amplify tau spreading in preclinical studies 4,5 . In contrast, age-related tau pathology typically occurring in the medial temporal lobe rarely spreads widely into the neocortex in the absence of cortical Aβ 6,7 , suggesting that the progression of tau aggregates is modified by Aβ 1,5 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the histopathological interactions between global amyloid and medial temporal neuroinflammation (48) reported that, in relation to tau spread, amyloid appeared to interact with transentorhinal neuroinflammation which, in turn, triggered the spread of tau across the neocortex (Braak stages II-III), followed by a subsequent spread of tau across Braak stages III-IV and the associated brain regions. A sentiment that was supported a year later, among a group of researchers who concluded that a "moderate" Aβ level is required for tau within the neocortex to be detectable, and that >40 centiloid of global Aβ burden is required to induce an accelerated spread of tau (49).…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%